PROFIL HABITAT JULANG EMAS (Aceros Undulatus) SEBAGAI STRATEGI KONSERVASI DI GUNUNG UNGARAN, JAWA TENGAH - Nugroho Edi K, Margareta Rahayuningsih (Indonesian Journal of Conservation, 2013)
Whreathead hornbill (Aceros undulatus) found at Mount Ungaran that the Important Birds Areas (IBA) in Indonesia-set by Birdlife International. The purpose of this research is to examine the ecology of Wreathed Hornbill (Aceros undulatus) in Mount Ungaran, especially to analyze the vegetation and habitat profile as an effort to support their habitat conservation at Mount Ungaran. ÃÂ Vegetation profile made from the vertical structure of vegetation canopy closure, by making use of plot size measuring 60 x 20 m. Measurements were taken to the standing of vegetation, canopy closure, direction of the canopy, height canopy, a former branch of the vegetation height, and stem diameter. The results show the diversity of vegetation in 4 (four) research station, Banyuwindu, Mount Gentong, Gadjah Mungkur and Watuondo found 46 species categories of tree , 17 species categories of tiang, 27 speciesÃÂ category of pancang, 19 species of seedlings and 27 species of undergrowth vegetation, most commonly tree found in Mount Ungaran is Ficus sp, Litsea sp (Wuru Kembang) and salam klontong. Based on the observations the tree used as nest of Wreathed HornbillÃÂ is Salam Klontong and Litsea sp. While Ficus sp is a source of food for the hornbill, including Wreathed Hornbill. Keywods : Habitat profile, Wreathed Hornbill (Aceros undulatus), consevation ÃÂ Julang emas (aceros undulatus) ditemukan di Gunung Ungaran yang merupakan Daerah Penting Burung (DPB) di Indonesia oleh Birdlife International. Tujuan penelitian adalah menguji ekologi julang emas (aceros undulates) di Gunung Ungaran, khususnya untuk menganalisis vegetasi dan profil habitat sebagai upaya untuk menunjang konservasi habitat di Gunung Ungaran. Profil vegetasi dibuat dengan struktur tutupan vertikal, dengan ukuran 60 X 20 m. Pengujian dilakukan dengan meneliti vegetasi tegakan, tutupan, penutupan kanopi, arah kanopi, kanopi tinggi, mantan cabang ketinggian vegetasi, dan diameter batang. Hasil penelitian menunjukkan keragaman vegetasi di 4 (empat) stasiun penelitian, yakni Banyuwindu, Gunung Gentong, Gadjah Mungkur dan Watuondo menemukan 46 spesies kategori pohon, 17 jenis kategri tiang, 27 jenis kategori pancang, 19 jenis semai dan 27 spesies vegetasi lapis bawah. Pohon paling sering ditemukan di Gunung Ungaran adalah Ficus sp, Litsea sp (Wuru Kembang) dan salam klontong. Berdasarkan pengamatan pohon yang digunakan sebagai sarang julang adalah Salam klontong dan Litsea sp. Sementara Ficus sp merupakan sumber makanan bagi burung enggang, termasuk julang emas. Kata kunci: Profil habitat, julang emas, konservasi. ÃÂ